Understanding Achievement Motivation Among Scholarship Recipients in Higher Education - Dela Wulandari; Riyo Riyadi; Ratna Fitri Astuti; Sudarman Sudarman (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
This study explores the dynamics of achievement motivation among scholarship recipients in a higher education context. Although scholarships are generally expected to enhance academic motivation and support students’ needs, many recipients perceive that financial assistance alone does not directly strengthen their motivation to achieve. Using a qualitative descriptive design, data were collected through in-depth interviews with five scholarship beneficiaries. The data were analyzed using a systematic process of reduction, presentation, and conclusion drawing. The findings reveal that, in terms of choice, scholarships function not only as financial support but also as catalysts that strengthen students’ motivation, sense of responsibility, and academic focus. Persistence is shaped by internal factors such as personal aspirations, family values, and responsibility, as well as external factors including financial stability, routine mentoring, and performance expectations. In the dimension of effort, scholarship recipients demonstrate structured learning strategies, consistent study habits, and increased engagement in academic improvement activities. Overall, the study highlights that scholarships play a multidimensional role extending beyond financial assistance by fostering responsibility, perseverance, and disciplined learning behavior. These insights contribute to a deeper understanding of motivational mechanisms among students receiving financial aid and underline the importance of integrated academic and mentoring support within scholarship programs.